The Two Sides of the Mediterranean: Population Genomics of the Black Sea Urchin Arbacia lixula (Linnaeus, 1758) in a Warming Sea - Carlos Carreras; Víctor Ordóñez; Àlex García-Cisneros; Owen S. Wangensteen; Creu Palacín; Marta Pascual; Xavier Turon (Frontiers in Marine Science, 2021)
Global environmental changes may have a profound impact on ecosystems. In this context, it is crucial to gather biological and ecological information of the main species in marine communities to predict and mitigate potential effects of shifts in their distribution, abundance, and interactions. Using genotyping by sequencing (GBS), we assessed the genetic structure of a keystone species in the Mediterranean shallow littoral ecosystems, the black sea urchin Arbacia lixula. This bioengineer species can shape their communities due to its grazing activity and it is experiencing an ongoing expansion with increasing temperatures. The population genomic analyses on 5,241 loci sequenced in 240 individuals from 11 Mediterranean sampled populations revealed that all populations were diverse and showed significant departure from equilibrium. Albeit genetic differentiation was in general shallow, a significant break separated the western and eastern Mediterranean populations, a break not detected in previous studies with less resolutive markers. Notably, no clear effect of the Almería-Oran front, an important break in the Atlanto-Mediterranean transition, could be detected among the western basin populations, where only a slight differentiation of the two northernmost populations was found. Despite the generally low levels of genetic differentiation found, we identified candidate regions for local adaptation by combining different genomic analysis with environmental data. Salinity, rather than temperature, seemed to be an important driver of genetic structure in A. lixula. Overall, from a population genomics standpoint, there is ample scope for A. lixula to continue thriving and adapting in the warming Mediterranean.